Bacterial Communities and Culturable Petroleum Hydrocarbon Degrading Bacteria in Marine Sediments in the Northeastern South China Sea - Xu, Wenhui; Qiao, Yanlu; Wei, Jinxiao; Jiang, Qing; Xue, Jianliang (Frontiers in Environmental Science, 2022)
Marine oil spill pollution was one of the factors affecting the marine ecology of the northeastern South China Sea (nSCS). The submarine oil produced after the oil spill had a long-term impact on the microbial community in the sediment. In this study, 16S rRNA genes high-throughput sequencing and quantitative PCR were used to study the composition and distribution of bacterial communities in deep-sea sediments; meanwhile, petroleum hydrocarbon degrading bacteria were isolated, of which activity were detected. Proteobacteria and Planctomycetota were the main bacterial phyla found in the samples studied in this study. 29 bacterial strains capable of degrading petroleum hydrocarbons were isolated from S02 and S39 sediment samples, belonging to genus Stenotrophomonas, Pseudidiomarina, Sulfitobacter, Pseudomonas, Halomonas and so on. Strains from Stenotrophomonas degraded petroleum hydrocarbons efficiently. This research provided new insights into distribution pattern of benthic microbial community in the nSCS, and validated the degradation potential of petroleum hydrocarbons by indigenous bacteria.